2010
DOI: 10.1186/1743-422x-7-342
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a mycovirus associated with the brown discoloration of edible mushroom, Flammulina velutipes

Abstract: BackgroundA mycovirus previously identified in brown discolored fruiting bodies of the cultivated mushroom Flammulina velutipes was characterized. We tentatively named the virus the F. velutipes browning virus (FvBV).ResultsPurified FvBV particles contained two dsRNA genomes (dsRNA1 and 2). The complete sequence of dsRNA1 was 1,915 bp long, containing a single open reading frame (ORF) that encoded 580 amino acids of a putative 66-kDa RNA-dependent RNA polymerase (RdRp). dsRNA2 was 1,730 bp long containing a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…However recent reports of the incidence of a partitivirus in the cultivated mushroom Flammulina velutipes associated with abnormally slow growth and the production of brown discoloured fruiting bodies (Magae and Sunagawa, 2010), similar to the effects reported here for AfuPV-1, confirms that partitiviruses can cause such effects. Interestingly a comparison of the susceptibility of all the virus-free and virus-infected isolates documented here to the common antifungals, amphotericin B, flucytosine, fluconazole, itraconazole, voriconazole, posaconazole, caspofungin, icafungin and anidulafungin, as assessed by minimal inhibitory concentration values (Petrou and Shanson, 2000) revealed no significant differences between the isolates (data not shown).…”
Section: Fungal Isolatesupporting
confidence: 85%
“…However recent reports of the incidence of a partitivirus in the cultivated mushroom Flammulina velutipes associated with abnormally slow growth and the production of brown discoloured fruiting bodies (Magae and Sunagawa, 2010), similar to the effects reported here for AfuPV-1, confirms that partitiviruses can cause such effects. Interestingly a comparison of the susceptibility of all the virus-free and virus-infected isolates documented here to the common antifungals, amphotericin B, flucytosine, fluconazole, itraconazole, voriconazole, posaconazole, caspofungin, icafungin and anidulafungin, as assessed by minimal inhibitory concentration values (Petrou and Shanson, 2000) revealed no significant differences between the isolates (data not shown).…”
Section: Fungal Isolatesupporting
confidence: 85%
“…However, many recent reports challenge this view, and there are several studies describing partitiviruses associated with phenotypic changes. Magae and Sunagawa (24) found that the presence of an alphapartitivirus, Flammulina velutipes browning virus, correlates with brown discoloration of the host fungus. Bhatti et al (25) found that the presence of a gammapartitivirus in Aspergillus fumigatus caused significant reductions in radial growth and biomass.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the virus family Partitiviridae have bipartite double-stranded RNA (dsRNA) genomes that infect plants, fungi, or protozoa (23). Partitiviruses were previously considered to be cryptic, but some members of this virus family mediate phenotypic alterations or hypovirulence in their host fungi (24)(25)(26)(27). Vainio et al (15) showed that the Heterobasidion alphapartitivirus HetPV3-ec1 causes growth reductions in Heterobasidion abietinum, and Hyder et al (4) described both negative and positive associations for this virus species, depending on host strain and environmental conditions.…”
mentioning
confidence: 99%
“…In Europe, Cryphonectria hypovirus 1 (CHV1) infecting isolates of Cryphonectria parasitica have successfully been used commercially to control chestnut blight (Nuss, 2005). The infection caused by partitiviruses in different fungal species have been reported to cause variable effects on their growth or hypovirulence (Magae and Sunagawa, 2010;Bhatti et al, 2011;Xiao et al, 2014;Zheng et al, 2014;Zhong et al, 2014, Sasaki et al, 2016. Reduced fungal virulence or hypovirulence is generally connected to phenotypic changes, reduced mycelial growth, and sporulation as a result of virus infection (Hillman et al, 2018).…”
Section: Do the Fungal Viruses Affect Their Host?mentioning
confidence: 99%